Food texture and viscosity : concept and measurement - Bourne, Malcolm C. (Food science and technology international series., 2002)
Drawing together literature from a variety of fields, Food Texture and Viscosity, 2E, includes a brief history of this area and its basic principles. It reviews how texture and viscosity are measured, including the physical interactions between the human body and food, objective methods of texture measurements, the latest advances in texture-measuring instruments, various types of liquid flow, and more. This revised edition contains approximately 30% new material, including two new chapters on physics and texture and the correlation between physical measurements and sensory assessments. It now.